Svp vous pouvez m'aider . Dévlopper et réduire les expressions .A= 7x-9+8x+6 . B = (x-3) (x+6) C = (x - 1) ( x - 5 ) D= ( x+2) (x+4) +5x au carré - 3x - 6 . E = (x-3) (2x+6) -4 (x-2) . J E VOUS REMERCIE D4AVANCE ;

2

Réponses

2014-03-23T10:52:26+01:00
A=15x -3 B=x² +6x -3x -18 = x² +3x -18 C=x²-5x-1x +5 =x² -6x +5 D=x²+4x+2x+8 +5x² -3x -6 = 7x²+3x +2 E=2x²+6x -6 -18 -4x+8 =2x² +2x -16 voici j'espère que tu comprend
2014-03-23T10:59:01+01:00
A= 7x-9+8x+6  A= 15x-3
B = (x-3) (x+6) B = x*x + x*6 - 3*x -3*6B = x ² + 6x - 3x - 18B = x ² +3x -18
C = (x - 1) ( x - 5 )  C = x*x + x*(-5) - 1*x - 1*(-5)C = x ² -5x - 1x + 5 C = x ² -6x + 5
D= ( x+2) (x+4) +5x ² - 3x - 6 D= x*x + x*4 + 2*x +2*4 +5x ² - 3x - 6D= x ² + 4x + 2x + 8 + 5x ² - 3x - 6D= 6x ² + 3x + 2
E = (x-3) (2x+6) -4 (x-2) E= x*2x + x*6 - 3*2x -3*6 -4 (x-2)wE= 2x ² + 6x - 6x - 18 - 4*x -4*-2E= 2x ² + 6x - 6x - 18 - 4x + 8E= 2x ² - 4x - 10